Synthesis A Flexible Conductive Film of Poly 3,4-Ethylenedioxythiophene Polystyrene Sulfonate (PEDOT: PSS) Using Spray Pyrolysis Method - Fadhil Muhammad Tarmidzi; Setia Budi Sasongko (International Journal of Renewable Energy Development, 2018)
Popularity of conducting polymers are become widely known and researches for practical application also has been done. In order to developed a continuous process for industrial scale,  we have proposed a spray pyrolysis method to synthesis a flexible conductive film of Poly(3,4-ethylenedioxythiophene) poly(styrene sulfonate) (PEDOT:PSS) on poly(ethylene terephthalate) (PET) and annealed at different temperatures and spray distances. The optimum condition that resulting a best morphology was anneal at 90oC and 20 cm distance with electrical conductivity 4.5 S/cm. It was found that annealing at temperature higher than 90oC will resulting a stress to a film and formed crack due to a different thermal expansion, while at the distance higher than 20 cm resulting a loss of PEDOT:PSS droplets. IR spectra shows that there is no any sign of PEDOT:PSS degradation even at 110oC. SEM analysis also show that the thickness is well distributed and there is no any sign of crack formedArticle History: Received February 24th 2017; Received in revised form May 16th 2018; Accepted May 20th 2018; Available onlineHow to Cite This Article: Tarmidzi, F.M. and Sasongko, S.B. (2018) Synthesis A Flexible Conductive Film of Poly 3,4-Ethylenedioxythiophene Polystyrene Sulfonate (PEDOT:PSS) Using Spray Pyrolysis Method. Int. Journal of Renewable Energy Development, 7(2), 159-162.https://doi.org/10.14710/ijred.7.2.159-162